Purification of native histidine-rich protein 2 (nHRP2) from Plasmodium falciparum culture supernatant, infected RBCs, and parasite lysate - Balwan Singh; Jessica N. McCaffery; Amy Kong; Yong Ah; Scott Wilson; Sayan Chatterjee; Deepak Tomar; Michael Aidoo; Venkatachalam Udhayakumar; Eric Rogier (Malaria Journal, 2021)
Abstract Background Despite the widespread use of histidine-rich protein 2 (HRP2)-based rapid diagnostic tests (RDTs), purified native HRP2 antigen is not standardly used in research applications or assessment of RDTs used in the field. Methods This report describes the purification of native HRP2 (nHRP2) from the HB3 Plasmodium falciparum culture strain. As this culture strain lacks pfhrp3 from its genome, it is an excellent source of HRP2 protein only and does not produce the closely-related HRP3. The nHRP2 protein was isolated from culture supernatant, infected red blood cells (iRBCs), and whole parasite lysate using nickel-metal chelate chromatography. Biochemical characterization of nHRP2 from HB3 culture was conducted by SDS-PAGE and western blotting, and nHRP2 was assayed by RDT, ELISA, and bead-based immunoassay. Results Purified nHRP2 was identified by SDS-PAGE and western blot as a − 60 kDa protein that bound anti-HRP-2 monoclonal antibodies. Mouse anti-HRP2 monoclonal antibody was found to produce high optical density readings between dilutions of 1:100 and 1:3,200 by ELISA with assay signal observed up to a 1:200,000 dilution. nHRP2 yield from HB3 culture by bead-based immunoassay revealed that both culture supernatant and iRBC lysate were practical sources of large quantities of this antigen, producing a total yield of 292.4 µg of nHRP2 from two pooled culture preparations. Assessment of nHRP2 recognition by RDTs revealed that Carestart Pf HRP2 and HRP2/pLDH RDTs detected purified nHRP2 when applied at concentrations between 20.6 and 2060 ng/mL, performing within a log-fold dilution of commercially-available recombinant HRP2. The band intensity observed for the nHRP2 dilutions was equivalent to that observed for P. falciparum culture strain dilutions of 3D7 and US06 F Nigeria XII between 12.5 and 1000 parasites/µL. Conclusions Purified nHRP2 could be a valuable reagent for laboratory applications as well as assessment of new and existing RDTs prior to their use in clinical settings. These results ...